Identification of the Trophic State of the San Nicolas Lake, Namora-Peru Through the Quantification of Chlorophyll a, Nitrates, Phosphates and Transparency. - Ciriaco Mosqueira, J.E. (2021)
Eutrophication is a global problem that has been progressively destroying aquatic ecosystems; due to this, it was decided to evaluate and analyze one of the most representative lakes in the region: The San Nicolas lake, which is located in Namora district, province and department of Cajamarca in the north of Peru. The purpose of this study was the determination of the trophic state of this lake through the quantification of chlorophyll a, nitrates, phosphates, and transparency. Six sampling stations were determined; from them, samples were taken at 0 m, 1.5 m, and 3 m depth with a Van Dorn hydrographic bottle, and the parameters were analyzed in-situ, also including transparency with a Secchi Disc. After analyzing the samples, were determined: The Trophic State Index (TSI) of Carlson, modified by Aizaki et al., resulted in a TSI = 64.72 (eutrophic) for chlorophyll a and a TSI = 66.55 (eutrophic) for water clarity; and The Nutrient Eutrophication Index (EI) according to Karydis et al., which resulted in an EI = 2.53 (oligotrophic) for nitrates and an EI = 3.35 (mesotrophic) for phosphates.